Targeted Prostate Biopsy: How, When, and Why? A Systematic Review - Rebez, Giacomo; Barbiero, Maria; Simonato, Franco Alchiede; Claps, Francesco; Siracusano, Salvatore; Giaimo, Rosa; Tulone, Gabriele; Vianello, Fabio; Simonato, Alchiede; Pavan, Nicola (Diagnostics (Basel), 2024)
Objective: Prostate cancer, the second most diagnosed cancer among men, requires precise diagnostic techniques to ensure effective treatment. This review explores the technological advancements, optimal application conditions, and benefits of targeted prostate biopsies facilitated by multiparametric magnetic resonance imaging (mpMRI). Methods: A systematic literature review was conducted to compare traditional 12-core systematic biopsies guided by transrectal ultrasound with targeted biopsy techniques using mpMRI. We searched electronic databases including PubMed, Scopus, and Web of Science from January 2015 to December 2024 using keywords such as “targeted prostate biopsy”, “fusion prostate biopsy”, “cognitive prostate biopsy”, “MRI-guided biopsy”, and “transrectal ultrasound prostate biopsy”. Studies comparing various biopsy methods were included, and data extraction focused on study characteristics, patient demographics, biopsy techniques, diagnostic outcomes, and complications. Conclusion: mpMRI-guided targeted biopsies enhance the detection of clinically significant prostate cancer while reducing unnecessary biopsies and the detection of insignificant cancers. These targeted approaches preserve or improve diagnostic accuracy and patient outcomes, minimizing the risks associated with overdiagnosis and overtreatment. By utilizing mpMRI, targeted biopsies allow for precise targeting of suspicious regions within the prostate, providing a cost-effective method that reduces the number of biopsies performed. This review highlights the importance of integrating advanced imaging techniques into prostate cancer diagnosis to improve patient outcomes and quality of life.